USE OF Aspergillus repens lN THE MOULDING PROCESS OF DRIED FISH STICK MADE FROM LITTLE TUNA (Euthynnus affinis) - Hari Eko lrianto; Fran Santoso; Jamal Basmal; Ninoek lndriati (Indonesian Fisheries Research Journal, 2008)
Dried fish stick is a popular product in Japan and called as Arabushi. The product which has undergone moulding process known as Katsuobushr. So far, lndonesia, particularly North Sulawesi Province, exports dried fish stick to Japan.